“ANALISIS YURIDIS KEDUDUKAN AKTA PERUBAHAN PERSEROAN TERBATAS YANG DIBUAT OLEH NOTARIS NAMUN TIDAK MENDAPAT PERSETUJUAN MENTERI HUKUM DAN HAM” - BINSAR WIJAYA (PREMISE LAW JURNAL, 2016)
Articles of Amendment of a corporation are one of the important parts in a corporation because it contains the right and obligation which are obviously stipulated in the Agenda. Articles of amendment of statutes is the ones which guarantee legal certainty for stakeholders in it, but the problems arouse when it is stipulated in Article 21, paragraph 1 of Law No. 40/2007 on Corporation, it is not filed or requested: whether Articles of Amendment of statutes does not get approval from the Minister of Law and Human Resources as it is required in Article 21, paragraph 1 on the requirement to get the approval from the Minister will be cancelled by law or whether it becomes invalid because it does not get approval from the Minister, or whether it is cancelled by itself because it has passed the time limit for requesting to get approval from the Minister. Keywords: Position of Certificate, Articles of Amendment, Articles of Amendment which does not get Approval from the Minister of Law and Human Resources